Self-Regulated Learning Enhancing Scientific Literacy for Higher Educations in 21st Century Education: A Systematic Literature Review - Anisa Jaya Rahmawati; Gunarhadi Gunarhadi; M. Muchtarom (STAI Hubbulwathan Duri, 2023)
This study explores the importance of self-regulated learning to overcome the low level of scientific literacy in 21st-century education. This study aims to: (1) identify problems in scientific literacy, (2) explore the relationship between self-regulated learning to scientific literacy (3) explain the impact of self-regulated learning on scientific literacy. The research method uses qualitative research with a systematic literature review that analyses the literature on self-regulated learning and scientific literacy. The analysis uses Preferred Reporting Items for Systematic Review (PRISMA). The results of the study show that: (1) the problems in scientific literacy include: the relevance of the material in school to everyday life, a critical assessment of the credibility of research sources, scientific attitudes and scientific knowledge, and aspects of content, process, context and diversity of literacy (2) explores the relationship self-regulated learning in scientific literacy with self-efficacy, motivation, active learning, and engagement (3) this study finds that self-regulated learning has a positive impact on scientific literacy. This study illustrates the important role of self-regulated learning in overcoming the limitations of scientific literacy in universities.